Progression of esophageal dysplasia to cancer. (29th September 2014) - Appelman, Henry D.; Matejcic, Marco; Parker, M. Iqbal; Riddell, Robert H.; Salemme, Marianna; Swanson, Paul E.; Villanacci, Vincenzo
Abstract : The following, from the 12th OESO World Conference: Cancers of the Esophagus, includes commentaries on the evolution of low‐grade squamous and glandular dysplasia to invasive carcinoma; the mutational spectra of Barrett's esophagus and adenocarcinoma; the risk of p53‐immunoreactive glandular dysplasia compared to non‐immunoreactive mucosa for progression to cancer; the role of lectins in progression to adenocarcinoma; and the role of racemase immunoreactivity in the prediction of risk of adenocarcinoma.